2013
DOI: 10.1002/mus.23753
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal characterization of functional, morphologic, and biochemical adaptations in mouse skeletal muscle with hindlimb suspension

Abstract: Insight into these early changes in response to HS improves understanding of the molecular and functional changes that lead to muscle atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 35 publications
(91 reference statements)
12
46
3
3
Order By: Relevance
“…An additional aim of this study was to investigate the effects of testosterone on the gene and protein expression levels of some muscle hypertrophy and atrophy molecular targets after TS. TS resulted in downregulation of Igf1 mRNA in the SOL and EDL, an effect reported previously . We also showed that this effect was induced more rapidly in EDL muscle than in SOL muscle, suggesting that IGF‐1 may contribute more to initiation of the muscle loss in fast‐twitch than in slow‐twitch muscles during TS.…”
Section: Discussionsupporting
confidence: 82%
“…An additional aim of this study was to investigate the effects of testosterone on the gene and protein expression levels of some muscle hypertrophy and atrophy molecular targets after TS. TS resulted in downregulation of Igf1 mRNA in the SOL and EDL, an effect reported previously . We also showed that this effect was induced more rapidly in EDL muscle than in SOL muscle, suggesting that IGF‐1 may contribute more to initiation of the muscle loss in fast‐twitch than in slow‐twitch muscles during TS.…”
Section: Discussionsupporting
confidence: 82%
“…In our experiments, VX-745 treatment prevented increase of the ubiquitin expression during unloading. Expression of muscle-specific E3 ubiquitin ligases MAFbx and MuRF1 is activated shortly after unloading and peaks at the third day [16,26]. VX-745 treatment prevented unloading-induced increase in MuRF-1, whereas MAFbx expression was not affected.…”
Section: Discussionmentioning
confidence: 96%
“…Briefly, skeletal muscle from forelimbs and hind limbs of 2-to 3-weekold IR fl/fl Igf1r fl/fl mice was minced and digested in 2.5 mM CaCl 2 with 2.4 U/ml dispase (Grade II; Roche) and 1% collagenase B (Roche) for 20 minutes, with gentle pipetting twice. Homogenates were centrimRNA levels in fed MIGIRKOs and even observe a decrease in E3-ligase mRNA levels in muscle from fasted MIGIRKOs relative to controls, this is not unexpected, since models of chronic muscle atrophy (>21 days denervation, immobilization, or long-term spinal cord injury) in both humans and mice display no change or even a decrease in the key atrophy markers atrogin-1 and MuRF-1 (33)(34)(35)(36). However, FoxOs are the critical targets of IR/IGF1R, as deletion of these proteins rescued muscle atrophy and decreased E3-ligase expression.…”
Section: Primary Mouse Myoblast Isolationmentioning
confidence: 94%